TEACHING ADULTS FOREIGN LANGUAGE: PROBLEMS AND SOLUTIONS - Natalia Leonidovna Moskovskaya; Alexander Andreyevich Nazarkov (Вестник Северо-Кавказского федерального университета)
This article deals with the pressing issue of teaching foreign languages to adults, their psycho-pedagogical features which influence the process of learning, potential problems of the organization of teaching and their solutions.